Application of SWOT Analysis in Strategies for Increasing the Competitiveness of Muslim Traders to Face the Asean Economic Community (AEC) - Ernayanti, Tri (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This study aims to find out how Islam views free trade, and to find out how Rabbani's strategy formulation is prepared in dealing with MEA by using SWOT analysis. Methodology:The strategy used by Rabbani in doing business is to establish a Muslim fashion business with a reshare system, because using this system the risks are much smaller than using other systems. Apart from that, in trying, an entrepreneur must always be passionate, tenacious, never give up and be able to read the opportunities that exist, that is what makes Rabbani successful. Main Findings: The success of Rabbani Muslim clothing in doing business in terms of customer service and the quality of the products offered has caused Rabbani Muslim clothing to continue to increase. However, to gain a larger market share, Rabbani Muslim fashion can increase the variety of Muslim clothing/veil products and open several outlets to other potential areas intensively. Novelty/Originality of this study: This study analyzes a trade process using swot analysis in dealing with the Asean economy so that a study is carried out on Muslim clothing, namely rabbani.